Ekspektasi Pengunjung Situs Reservasi Hotel Online: E-wom dalam Menciptakan Keputusan Pembelian - Hijrianti, Rina A.; Wibowo, Lili Adi; Dirgantari, Puspo Dewi (Universitas Pendidikan Indonesia, 2019)
The purpose of this research is to find out the influence of e-wom toward purchase decision on online hotel reservation visitors in Indonesia. A total of 200 respondents were selected using probability sampling. A questionnaire was used as a resreach instrument to collect data from respondents. The analysis tehnique by using frequency distribution.